REVIEW OF THE CORRELATION BETWEEN SALIVARY PROINFLAMMATORY CYTOKINES IN CHRONIC KIDNEY DISEASE AND PERIODONTAL DISEASE IN CHILDREN - Vacariu Simina Mădălina; Adumitroaie Alina Elena; Tuluc Iulian; Cioloca Daniel; Iuliana Magdalena Stârcea; Munteanu Mihaela; Savin Carmen Nicoleta; Toma Vasilica (Romanian Dental Association for Education, 2021)
Objectives: The purpose of this review was to evaluate the literature on saliva analysis in diagnosing chronic kidney disease or periodontal disease, as well as to establish a possible correlation between biomarkers analyzed in children with chronic kidney disease (CKD) and periodontal disease (PD). Emphasis was placed on some proinflammatory cytokines (tumor necrosis factor (TNF-α) and interleukin 6 (IL-6)), found in both chronic kidney disease and periodontal disease. Material and method: We evaluated articles from the MedLine database, researched via PubMed, using MeSH terms. Results: Since periodontal disease is a common oral pathology in patients with chronic kidney disease, it is essential to distinguish whether the modification of salivary biochemical markers is caused by the alteration of the general immune system, or the existent periodontal pathology. Also, an alternative, non-invasive process to blood analysis in children would be extremely beneficial. Conclusions: Saliva analysis is a simple, non-invasive diagnostic test, fast and easy to accept by the paediatric patient and which could be a substitute for serum or plasma in the diagnosis of CKD, but in terms of the correlation between specific biomarkers seen in children with chronic kidney disease and periodontal disease, further studies are necessary to determine their interdependence and clinical relevance.